2002
DOI: 10.1302/0301-620x.84b8.0841145
|View full text |Cite
|
Sign up to set email alerts
|

Application of locked intramedullary nails in the treatment of complications after distraction osteogenesis

Abstract: istraction osteogenesis (callotasis) has been widely used in patients with limb-length inequality or massive bone defects. This procedure, however, may be associated with a high incidence of physical and psychosocial complications. Callotasis telescoping on a locked intramedullary nail has been used to shorten the period of external fixation. Little attention has been given to the use of locked intramedullary nails in the treatment of complications after callotasis.Between 1990 and 1999, we used locked intrame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 19 publications
0
3
0
1
Order By: Relevance
“…Lai et al [19] reported the use of locked intramedullary nails in the treatment of complications after distraction osteogenesis including nonunion at lengthening and docking sites. They achieved 100% bony union in 27 patients and had a deep infection rate of 7%.…”
Section: Discussionmentioning
confidence: 99%
“…Lai et al [19] reported the use of locked intramedullary nails in the treatment of complications after distraction osteogenesis including nonunion at lengthening and docking sites. They achieved 100% bony union in 27 patients and had a deep infection rate of 7%.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 However, early removal of the external fixator and replacement by intramedullary nail achieved the same clinical and functional outcome as the classic technique with a shorter duration of external fixation. [27][28][29] Furthermore, the suggested adequate time to perform nailing was when callus formation was radiographically visible at the distraction site because the intramedullary implant could occupy the healing space for osteogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Under these circumstances, in those cases where an additional stabilisation of the lengthening callus or an enhancement of the biological environment for callus growth or union at the docking side was considered necessary, we convert our technique to intramedullary nailing [13,17,19]. The functional, emotional and psychological status of our patients was improved immediately after fixator removal, especially in those cases with prolonged time of application (up to 2 years).…”
Section: Discussionmentioning
confidence: 99%